Dialog Antara Prinsip-Prinsip dan Nilai-Nilai Koperasi dengan Modal Sosial di Koperasi Kredit Marsudi Mulyo, Putat Patuk Gunung Kidul - Rizki Emelia Sinuraya (Magister Administrasi Publik, 2012)
Koperasi Kredit Marsudi Mulyo, adheres to trust, honesty and cooperation as core values with respect to its establishment, membership, business management and conduct of social activities. Specifically for membership, principles encompass self-responsibility, equality, open and voluntary membership, democratic, autonomy, freedom, togetherness and the opportunity to undergo training and education; in business management principles employed include self-reliance, economic participation, justice, solidarity, transparency, honesty, tolerance and cooperation; while in the conduct of social activities, principles used encompass solidarity,mutual help, mutual aid and concern. The values and principles create an atmosphere of kinship, mutual help and mutual cooperation in generating trust, which allows fellow members to cooperate in developing networks by exchanging virtues based on shared values.